Comparison of Chemical Composition, In Vitro Digestibility, and Near Infrared Reflectance Spectroscopy in Estimating In Situ Rumen Degradable Protein of Tropical Foliage - Despal; Y. I. Yulianti; R. Zahera; I. Agustiyani; A. Rosmalia; I. M. Afnan; M. Zain; U. H. Tanuwiria (Faculty of Animal Science, Bogor Agricultural University, 2023)
Tropical foliage is an alternative source for protein enrichment in the dairy ration. However, due to the expensive, laborious, and time-consuming data-gathering method, its degradability database for inclusion in ration formulation is still lacking. This study aims to estimate tropical foliage's in situ protein degradability (RDP) using chemical compositions, in vitro digestibilities, and near infrared reflectance spectroscopy (NIRS) methods. The study used one hundred ten tropical foliage samples and observed chemical composition, in vitro dry and organic matter digestibility, and in situ degradation characteristics variables. NIRS spectra were collected to calibrate and validate the in situ degradation characteristics. Correlations were made prior to regression analysis. The results showed that tropical foliage varied in ash (3.02%-18.3%), crude protein (CP) (11.6%-30.7%), crude fiber (CF) (10.2%-29.8%), neutral detergent fiber (NDF) (31.0%-58.2%), acid detergent fiber (ADF) (18.7%-44.1%), dry matter digestibility (DMD) (23.9%-73.2%), organic matter digestibility (OMD) (25.6%-73.9%), and in situ RDP (21.0%-75.4%). The foliage was highly degraded (RDP > 60%) except for Calliandra calothyrsus (59%). In situ RDP significantly correlated with ash, CP, CF, DMD, and OMD with coefficient correlations (r) of 0.43, 0.60, -0.33, 0.74, and 0.76, respectively. Estimation of RDP using chemical composition and in vitro digestibility followed the equation: RDP (%)= 0.69 + 2.122 CP (%) with R²= 0.41 (p<0.01) and RDP (%)= 0.162 ash + 1.270 CP -0.104 CF + 0.489 IVOMD, with R²= 0.68, p<0.01). Calibration of NIRS using in situ RDP resulted in a regression coefficient (R²) of 0.78. It is concluded that RDP tropical foliage can be estimated more accurately using NIRS compared to in vitro digestibility and chemical composition.